Kendali Sudut Pitch dan Roll fase Lepas Landas pada Pesawat VTOL-plane - Sembiring, Jaka Persada; Rossi, Farli; Susanto, Try (Majalah Ilmiah Teknologi Elektro, 2022)
Abstract —VTOL-plane is a hybrid vehicle that combines a fixed-wing vehicle and a rotary-wing vehicle with the advantages of good endurance and good maneuverability. Combining these two types of UAVs requires a control system capable of stabilizing the shift from fixed-wing to rotary-wing mode or vice versa. Attitude disorientation occurs in the form of a decrease in height due to overshoot. therefore, a mode or control many input parameters. The Linear Quadratic Regulator (LQR) control method is one of the control methods capable of producing minimum errors and capable of many input parameters. The LQR control system produces a control response with a rise time according to the needs. The LQR control meets the specifications of the VTOL-plane vehicle requirements to handle minimum errors. Attitude disorientation occurs due to overshoot, as well as handling of the control system which can only handle a small amount of input and output on the VTOL-plane vehicle. Keyword - Control, LQR, Overshoot, UAV.